Scale to Assess the Sustainability of Rice-Wheat Cropping System (Indian Journal of Extension Education, 2022)
Rice-Wheat Cropping System (RWCS) is a principle cropping system followed in Indo Gangetic Plains (IGP). Though this monocropping system plays a key role in India’s food sufficiency, it has led to various problems such as soil degradation, groundwater exploitation, environmental damage, yield plateau etc., posing challenge and risk to its sustainability. The scale was developed during 2021-22 to assess the perception level of farmers about the sustainability issues in RWCS. Summated rating scale method by Likert with standardized procedures was used to develop this scale. A total of 54 items were collected and sent to experts for relevancy analysis. Based on the results of relevancy analysis, a schedule consisting of 43 items was used to conduct personally interviewed pre-test. The items were further screened for their differentiating ability and thus, the final scale consisted of 31 items. The scale was found to be valid and reliable as ascertained by content validity and split half test reliability method, respectively. The reliability coefficient of 0.884 indicated the higher internal consistency.